2015
DOI: 10.1101/gr.191296.115
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome profiling reveals an important role for translational control in circadian gene expression

Abstract: Physiological and behavioral circadian rhythms are driven by a conserved transcriptional/translational negative feedback loop in mammals. Although most core clock factors are transcription factors, post-transcriptional control introduces delays that are critical for circadian oscillations. Little work has been done on circadian regulation of translation, so to address this deficit we conducted ribosome profiling experiments in a human cell model for an autonomous clock. We found that most rhythmic gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
112
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 74 publications
13
112
2
Order By: Relevance
“…These data lead to additional questions: (i) To what extent does clock control of translation elongation affect rhythmic protein levels, and (ii) what is the advantage of clock control of translation elongation to the organism? Recent ribosome profiling in mammalian cells revealed that ∼10% of mRNAs with rhythmic ribosome occupancy lacked corresponding rhythmic mRNA levels (56,57). In the mouse liver, rhythmic ribosome occupancy on ∼500 constitutively accumulating mRNAs was enriched for mRNAs containing 5′-Terminal Oligo Pyrimidine (TOP) tracts, or Translation Initiator of Short 5′-UTR (TISU) elements (58).…”
Section: Discussionmentioning
confidence: 99%
“…These data lead to additional questions: (i) To what extent does clock control of translation elongation affect rhythmic protein levels, and (ii) what is the advantage of clock control of translation elongation to the organism? Recent ribosome profiling in mammalian cells revealed that ∼10% of mRNAs with rhythmic ribosome occupancy lacked corresponding rhythmic mRNA levels (56,57). In the mouse liver, rhythmic ribosome occupancy on ∼500 constitutively accumulating mRNAs was enriched for mRNAs containing 5′-Terminal Oligo Pyrimidine (TOP) tracts, or Translation Initiator of Short 5′-UTR (TISU) elements (58).…”
Section: Discussionmentioning
confidence: 99%
“…Translation efficiency is estimated by comparing ribosomal occupancy to transcript abundance. This approach was applied to human cell line (Jang et al 2015) and mouse liver around the clock (Atger et al 2015;Janich et al 2015). The results suggested that, for most genes, when transcription fluctuates in a circadian manner, mRNA accumulation and protein synthesis follows.…”
Section: Circadian Regulation In Translation Efficiencymentioning
confidence: 99%
“…Protein synthesis can be rhythmic from mRNAs whose abundances are constant. Conversely, mRNA abundance can be rhythmic but lead to flat ribosomal occupancy (Atger et al 2015;Jang et al 2015;Janich et al 2015). For example, iron metabolism mRNAs accumulate constantly but are rhythmically translated in mouse liver (Janich et al 2015).…”
Section: Circadian Regulation In Translation Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The mutant cells cannot limit the abundance of the transcriptional repressor Yox1, likely because PBs fail to repress properly the translation of Yox1 mRNA. Interestingly, the circadian clock controls PB formation [35]. Thus, it is possible that DNA repair or regulatory switches associated with PBs undergo rhythmic changes.…”
Section: Rna Granules Generated In the Absence Of Stressmentioning
confidence: 99%